Small Open Space - Karki, Rachana; Maharjan, Bipin; Subedi, Dinesh; Kumar Kalwar, Aadesh; Shrestha, Sweta (KEC Journal of Science and Engineering, 2024)
People can participate in the public realm by using public open spaces. In contrast to the setting of home or job, it is a place where people can physically join the larger community. The absence of neighbour interactions and the isolation of people as a result of a lack of well-maintained public open spaces have been characteristics of a new emerging town. Many public open places around the world have been underappreciated and severely neglected. A well-planned public open space would entice residents to leave their homes and participate in a variety of activities. When it comes to use and occupancy, this can raise the quality of the area. By evaluating the architectural and urban elements of the public open spaces, this research intends to discover and analyse dysfunctional public open spaces and weak linkages in those areas, and come up with solutions to improve these spaces and stimulate public life.